PHOTOGRAPHIC OBSERVATIONS OF MAJOR PLANETS AND THEIR MOONS DURING 1961-1990 AT THE MAO NAS OF UKRAINE - Yizhakevych, O. M.; Andruk, V. M.; Pakuliak, L. K. (Одеські астрономічні публікації, 2016)
We present the results of photographic observations’ processing of Saturn’s moons, Uranus, Neptune and their moons on the basis of MAO NAS of Ukrainephotographic observational archive. The analysis of the results is given. Observations were obtained using 4 telescopes: Double Long-Focus Astrograph (DLFA, D/F = 400/5500), Zeiss Double Astrograph (DAZ, D/F= 400/3000), Reflector Zeiss-600 (D/F= 600/7500), Wideangle Astrograph, (DWA, D/F= 400/2000). Observations were carried out during 1961 – 1990 (http://gua.db.ukrvo. org). Digitizing of plates has been done by EPSON EXPRESSION 10000XL (EE) flatbed scanner in 16-bit gray color range with resolution 1200dpi.( Andruk et al.: 2005, 2012; Golovnja et al.: 2010;. Protsyuk et al. 2014a, 2014b). The reduction of plates was made using the software developed in MAO NASU in the enhanced LINUX-MIDAS software kit. (Andruk V. et al.: 2016a, 2016b). Tycho2 was used as a reference system. The internal accuracy of the reduction for the first three instruments is ±0.08 – ±0.13 arcsec for both coordinates. For the wide angle astrograph DWA, RMS errors appeared 2 – 2.5 times higher. The total amount of processed plates with images of Saturn’s moons is 209 (511 frames), 33 plates contain the images of Uranus and U1,U2,U3,U4 moons, 29 plates have images of Neptune and N1 moon (Yizhakevych et al., 2015, 2016, 2017; Protsyuk et al., 2015). The online comparison of calculated positions of objects with IMCCE ephemeris data was made (http://lnfm1.sai.msu.ru/neb/nss/nssephmf.htm).